Monetary policy and the spot exchange rates : efficiency markets - rational expectations approach - Ghartey, Edward E. ([Caribbean Centre for Money & Finance] St. AugustineTT, 1995)
Seeks to measure the efficiency of the FEM to assist in the policy making process of the central bank and the government.